Fat soluble vitamins deficiency in pediatric chronic liver disease: The impact of liver transplantation. Issue 3 (March 2020) - Veraldi, Silvio; Pietrobattista, Andrea; Liccardo, Daniela; Basso, Maria Sole; Mosca, Antonella; Alterio, Tommaso; Cardile, Sabrina; Benedetti, Sabina; Della Corte, Claudia; Candusso, Manila
Abstract: Background: Children affected with chronic liver disease are at risk for fat-soluble vitamins (FSV) deficiency, in this scenario the role of liver transplant has been only partially explored. Aims: This study aimed to evaluate the prevalence of FSV deficiency in a cohort of paediatric patients awaiting liver transplant, analyze relationships between plasma vitamin concentrations and risk of acute rejections and liver fibrosis and assess the impact of the transplant on vitamin status. Methods: 166 children candidates for liver transplant were retrospectively evaluated. Vitamin concentrations were measured before and 12 months after transplantation. Results: Before transplant vitamin A, vitamin E and vitamin D deficiency was found in 66.6%, 40.6% and 36.3% of patients, respectively. 12 months after surgery, the prevalence of deficiency decreased to 29, 5% and 2, 6% for vitamin A and E while remained the same for vitamin D (36.3%). No association was found between vitamin status and the risk of acute rejections or the severity of liver fibrosis. Conclusion: Liver transplant was effective to improve vitamin A and E, but it did not affect vitamin D. A consensus is needed to define optimal nutritional management of these patients in order to prevent deficiencies.